Influences on people's choice of Ayurvedic healing. - Lalbahadur, Yajna (My University, 2013)
South Africa hosts a plural healthcare system that includes an allopathic sector and a complementary and alternative healthcare sector. This research report seeks to understand the motivations behind why people use the complementary system of Ayurveda, in South Africa and how they decide on its use through processes governing their decision making methods. The literature review summarises the key theoretical framework which moulded the study. The themes incorporated in the review include medicine’s evolution, Ayurveda, medical pluralism and complementary and alternative medicine, the illness experience and help seeking behaviour, the sick role and its relation to help seeking behaviour, and the Health Belief Model. The research was qualitative in nature and entailed semi structured interviews that were conducted with twenty seven Ayurveda users and three Ayurvedic doctors. The findings and analysis draw on the literature review, and when analysed, are developed into three coherent themes namely Ayurveda in South Africa (sets the scene of Ayurveda within the country), Reasons for using Ayurveda (the motivations behind people’s help seeking behaviours toward the system), and the use of Ayurveda in relation to other healing systems. The research found that Ayurveda is currently undergoing resurgence in South African society and in the process links itself to the wider global context that Ayurveda has situated itself. We also discover that participant’s decisions on the use of Ayurveda were decided upon through a multitude of factors and often Ayurveda was also utilised in many different situations rather than for a single case. Such interconnecting factors include their socialisation, lay referrals, interest in alternative systems, a sense of Indian pride and a cynical perception of Western medicine. Alternative or complementary system use was decided upon through factors that linked to people’s access of the alternative services and its affordability. Decisions ultimately were made to use Ayurveda as a complementary system to allopathy. Finally the conclusions of the study indicate that Ayurveda was transferred to South Africa, from India, through the country’s system of indentured labour where knowledge of the practice was passed down along generations. The research also deduces that it is primarily the Indian race that uses Ayurveda in South Africa and as such the healing system is more prominent in Indian areas. In addition, Ayurveda was not found to be a viable health or healing option for the wider South African population for whom its affordability and accessibility pose barriers.
Keywords: Medicine, Ayurvedic--South Africa.; Alternative medicine--South Africa.